Influence of Leadership and Employee Benefits to the Quality of Employees in Production - Faraj, Mohammed Alsaghir; , Drs. Farid Wajdi, M.M., Ph.D; , Drs. Ahmad Mardalis, M.BA (2014)
The purpose of this study is analysing leadership has positive effect to the quality of employee in production at PDAM of Surakarta and employee benefit has positive effect to the quality of employee in production at PDAM of Surakarta. This research is quantitative, by taking samples at PDAM of Surakarta, Central Java, Indonesia. The study population and sample as many as 400 employees were taken by 40 employees. The technique of collecting data using questionnaires. The data analysis technique used is multiple linear regression analysis. The results obtained showed that: Leadership has positive effect to the quality of employee in production at PDAM of Surakarta and employee benefit has positive effect to the quality of employee in production at PDAM of Surakarta.